Chapter 9: Indigenous Data Sovereignty: Implications for Data Journalism - Kukutai, Tahu; Walter, Maggie (The Data Journalism Handbook: Towards a Critical Data Practice, 2021)
Keywords: indigenous data sovereignty

Beyond the “Abyssal Line”: Knowledge, Power, and Justice in a Datafied World - Cormack, Donna; King, Paula (The Oxford Handbook of Indigenous Sociology, 2021)
Colonization fundamentally disrupted Indigenous knowledge systems, establishing epistemic hierarchies that privilege Eurocentric colonial epistemologies and methodologies. In this chapter, the authors explore how epistemic hierarchies are (re)produced in the current context of “big data” and datafication, in particular for mokopuna Māori in the nation-state known as New Zealand (NZ). (We use the concept of “mokopuna Māori” to refer to and position Māori babies, children, and young people within the Māori world as the sacred reflection of our ancestors and a blueprint for future generations.) The chapter then considers the possibilities for Indigenous epistemic justice in the “zone of nonbeing” or beyond the “abyssal line.”
Keywords: colonial methodology; colonisation; data; data sovereignty; heirarchy; kaupapa māori; methodology